Evaluating the influence of treated banana fiber on the strength of soil subgrade - Datuin, Zachary O. (Animo Repository, 2022)
The Philippines is a country rich in Acrisol soils which are characterized by their clay content. Clayey soils possess unfavorable engineering properties and are particularly loose, soft, and expansive materials making it hazardous to build structures over them. In the case of a subgrade or slopes with unsuitable soil, the engineer may require the contractor to remove the unsuitable material and backfill it with suitable material. An alternative to this is incorporating soil stabilization techniques in order to mitigate the unfavorable conditions that unstable soil may cause. Aside from Acrisol soils, the Philippines is also rich in banana production, which leads to 2.3 million metric tons of banana stems being thrown to waste. Several studies suggested the use of banana fibers as soil reinforcements may improve the mechanical properties of soil such as the shear strength and CBR value. However, the chemical composition of banana fibers is largely composed of lignin, hemicellulose, and wax which limit the mechanical properties and adhesion of the banana fibers. In order to address this, chemical treatments were performed on the banana fibers in order to extract and wash away lignin, hemicellulose, and wax, and to further improve their mechanical properties. In this study, banana fibers were extracted and treated with 1%, 3%, 5% Alkali, and 5%, 10%, 15% Sodium Lauryl Sulfate (SLS), after which the fibers were binded with polyvinyl acetate (wood glue) to form non-woven banana fiber sheets. The effect of treated banana fiber reinforcements on the compressive strength of soil was tested through the California Bearing Ratio (CBR) test and Unconfined Compressive Strength (UCS) test. Based on the results, the banana fiber sheets tend to improve the CBR ratio and the unconfined compressive strength of the soil. It was also found that the SLS-treated banana fiber sheets yielded greater results than the alkali-treated banana fiber reinforcements under unsoaked conditions, while the opposite was true under soaked conditions. One-way Analysis of Variance was used as a statistical tool to compare and assess the treatments applied to the Banana Fibers. It was found that there is no significance or there is mostly no relationship between the two variables which are the treatments with varying percentages and the CBR and UCS results.